Formação continuada colaborativa de professores: mediações e contrapalavras - Ortega, Leliane Regina (2020)
This research focuses on the Collaborative Continuing Education (CCE) of teachers in the early years of elementary school, aimed at working with the discourse genres in Portuguese Language teaching. In addressing this topic and its purposes, we seek to answer the following questions: What knowledge about the genres of discourse are consolidated by teachers participating in an CCE proposal? In an CCE process, can collaboration be developed between participating teachers and researcher through theoretical and methodological reflections on discursive genres? What responses reverberate in the didactic elaborations of the participants, from the mediation actions that took place at the CCE? Based on these questions, we outlined as a general objective: to analyze the contributions of mediation of theoreticalmethodological knowledge about the genres of discourse in the teaching of Portuguese Lenguage in a CCE developed with 3rd, 4th and 5th grade teachers - initial years. The theoretical-methodological foundation is based on the Dialogical Conception of Language, on Historical-Cultural Theory and on researchers on the subject of continuing education of teachers, such as Magalhães (2004, 2011); Liberali (2004), Pimenta (2005, 2012), Costa-Hübes (2008) among others. The investigative process is inscribed in Applied Linguistics, supported by the interpretative qualitative approach and inserted in the critical-collaborative action research. The data were generated in three moments: first, we traced the diagnostic profile of the collaborating teachers (initial interview, pedagogical plans and class diaries); then, we planned and developed the FCC actions (study meetings and reflections, research, didactic elaboration and development of the activities elaborated in the classroom); and, finally, we analyze how the mediation actions impacted the didactic elaborations, analyzing if the knowledge worked during the CCE was internalized/appropriated and exteriorized through the active response of the collaborating teachers. After analyzing the data, we highlight the following results with the FCC: a) appropriation of scientific concepts and knowledge concerning the dialogical conception of language; b) reflections and critical analysis on other teaching practice; c) didactic elaborations for the work with the genres of discourse in the context of teaching Portuguese Language to students of the initial years, reverberating theoretical-methodological aspects problematized during the CCE; d) autonomy, security and creativity in decision making for the work with the genres in the classroom. Therefore, the FCC modality, when developed through diversified mediations, proved to be relevant for teacher education, mainly because it allows the production of counterwords and researcher and contributes for the theoretical-methodological knowledge about the work with the discourse genres in Portuguese language teaching to be appropriated/internalized.